Pengaruh Reward dan Punishment terhadap Cyberloafing dengan Stres kerja menjadi pemediasi pada Dosen di Kota Bengkulu - Okka Adittio Putra; Fauzan Fauzan; Hananda Fitra Pranatha (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
This study aims to analyze the effects of rewards and punishment, mediated by job stress, on cyberloafing behavior among lecturers in Bengkulu City. The research background is rooted in the prevalence of personal internet use during work hours (cyberloafing) in academic environments, which negatively impacts productivity. A quantitative method using Partial Least Squares - Structural Equation Modeling (PLS-SEM) was employed to analyze data from 100 lecturers at state (PTN) and private (PTS) universities in Bengkulu, selected through purposive sampling. The results indicate that rewards have a significant negative effect on cyberloafing (β = -0.45; p = 0.001) and job stress (β = -0.32; p = 0.003), while punishment has a significant positive effect on cyberloafing (β = 0.32; p = 0.020) and job stress (β = 0.28; p = 0.011). Job stress was proven to mediate the relationship between rewards, punishment, and cyberloafing (indirect effects: -0.14 and 0.13; p < 0.05). The implications highlight the importance of fair reward policies and educational approaches in implementing sanctions to reduce job stress and cyberloafing in higher education settings.